Several factors of tooth decay in students 2 secondary schools in Thai Binh City in 2020 (Vietnam Journal of Community Medicine, 2022)
A descriptive cross-sectional study on 424 students to assess the knowledge and practice of oral care and some factors related to dental caries of students at 2 secondary schools Ky Ba and Phu Xuan, Thaibinh city. Research results show that: Female students (64.8%) have a higher risk of tooth decay than male students (35.2%) with p < 0.05 (OR=2.35; 95%CI: 1.55-3.56). There is a difference in tooth decay in urban and rural areas: students at Phu Xuan school have a higher rate of tooth decay than students at Ky Ba school (46.6%; 25.7%; p
Keywords: Factors related to tooth decay, secondary schools student.